Challenging the specificity of chlorzoxazone and 4-nitrophenol as marker substrates for CYP2E1 activity in Supersomes™ - Anna Hellmann; Ann-Kathrin Lenich; Stephanie Ruez; Jörg Fahrer; Jasmin Lott; Michelle Schaefer (Archives of Toxicology, 2026)

HESI GTTC ring trial: Concordance between Ames and rodent carcinogenicity outcomes for N-nitrosamines (NAs) with rat and hamster metabolic conditions - Joel Bercu; Alejandra Trejo-Martin; Connie Chen; Maik Schuler; Jennifer Cheung; Tetyana Cheairs; Anthony M. Lynch; Dean Thomas; Andreas Czich; Aisar Atrakchi; Timothy J. McGovern; Robert H. Heflich; et al. (Regulatory Toxicology and Pharmacology, 2025)

Detection of the clinically persistent, pathogenic yeast spp. Candida auris from hospital and municipal wastewater in Miami-Dade County, Florida - Kristina Babler; Mark Sharkey; Sebastian Arenas; Ayaaz Amirali; Cynthia Beaver; Samuel Comerford; Kenneth Goodman; George Grills; Michelle Holung; Erin Kobetz; Jennifer Laine; Walter Lamar; et al. (Science of The Total Environment, 2023)

Detection of numerous phycotoxins in young bull sharks (Carcharhinus leucas) collected from an estuary of national significance - Michelle L. Edwards; Adam M. Schaefer; Malcolm McFarland; Spencer Fire; Christopher R. Perkins; Matthew J. Ajemian (Science of The Total Environment, 2023)

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)

A novel phylogenetic regionalization of phytogeographical zones of southern Africa reveals their hidden evolutionary affinities - Barnabas H. Daru; Michelle van der Bank; Olivier Maurin; Kowiyou Yessoufou; Hanno Schaefer; Jasper A. Slingsby; T. Jonathan Davies (Journal of Biogeography, 2016)
Aim Although existing bioregional classification schemes often consider the compositional affinities within regional biotas, they do not typically incorporate phylogenetic information explicitly. Because phylogeny captures information on the evolutionary history of taxa, it provides a powerful tool for delineating biogeographical boundaries and for establishing relationships among them. Here, we present the first vegetation delineation of the woody flora of southern Africa based upon evolutionary relationships. Location Southern Africa. Methods We used a published time‐calibrated phylogenetic tree for 1400 woody plant species along with their geographical distributions and a metric of phylogenetic beta diversity to generate a phylogenetic delineation of the woody vegetation of southern Africa. We then explored environmental correlates of phylogenetic turnover between them, and the evolutionary distinctiveness of the taxa within them. Results We identified 15 phylogenetically distinct biogeographical units, here referred to as phyloregions. The largest phyloregion broadly overlaps with Savanna vegetation, while the phyloregion overlapping with the south‐western portion of the Fynbos biome is the most evolutionarily distinct. Potential evapotranspiration and mean annual temperature differ significantly among phyloregions and correlate with patterns of phylogenetic beta diversity between them. Our phylogeny‐based delimitation of southern Africa's woody vegetation broadly matches currently recognized phytogeographical classifications, but also highlights parts of the Namib Karoo and Greater Limpopo Transfrontier Park as distinct, but previously under‐recognized biogeographical units. Main conclusions Our analysis provides new insights into the structure and phylogenetic relationships among the woody flora of southern Africa. We show that evolutionary affinities differentiate phyloregions closely resembling existing vegetation classifications, yet also identify ‘cryptic’ phyloregions that are as evolutionarily distinct as some of the recognized African vegetation types.